Multi-method study of the impact of fermentation on the polyphenol composition and color of Grenache, Cinsault, and Syrah rosé wines. (1st March 2023) - Leborgne, Cécile; Ducasse, Marie-Agnès; Meudec, Emmanuelle; Carrillo, Stéphanie; Verbaere, Arnaud; Sommerer, Nicolas; Bougreau, Matthias; Masson, Gilles; Vernhet, Aude; Mouret, Jean-Roch; Cheynier, Véronique
Highlights: Rosé musts from three varieties showed different phenolic compositions and colors. Depending on must compositions, different fermentation impacts were highlighted. Changes involved anthocyanin conversion to derived pigments and adsorption on lees. Anthocyanin reactions during Syrah must fermentation had limited impact on color. Adsorption of higher molecular weight pigments on lees resulted in color loss. Abstract: Rosé wines show large color diversity, due to different phenolic pigment compositions. However, the mechanisms responsible for such diversity are poorly understood. The present work aimed at investigating the impact of fermentation on the color and composition of rosé wines made from Grenache, Cinsault, and Syrah grapes. Targeted MS analysis showed large varietal differences in must and wine compositions, with higher concentrations of anthocyanins and flavanols in Syrah. UV–visible spectrophotometry and size exclusion chromatography data indicated that Grenache and Cinsault musts contained oligomeric pigments derived from hydroxycinnamic acids and flavanols which were mostly lost during fermentation due to adsorption on lees. Syrah must color was mainly due to anthocyanins which were partly converted to derived pigments through reactions with yeast metabolites with limited color drop during fermentation. This work highlighted the impact of must composition, reflecting varietal characteristics, on changes occurring during fermentation and consequently wine color.